Thermal and photochemical mechanisms for cyclobutane formation in bielschowskysin biosynthesis - Tang, Bencan; Simion, Robert; Paton, Robert S. (Thieme, 2015)
The unique structure of furanocembranoid natural product bielschowskysin has provoked a number of biosynthetic hypotheses: quantum chemical calculations provide a means to assess the feasibility of postulated mechanisms in the construction of this unusual carbon skeleton. Calculations reveal that thermal closure is possible in water via an unusual concerted cyclobutane-forming transition state without the intervention of an enzyme. Photocycloaddition is computed to be extremely efficient, provided enol ether triplet sensitization can be achieved by an appropriate light source. The possible existence of a stable dicarbonyl intermediate presents a challenge for the thermal route, implicating a photochemical pathway in bielschowskysin biosynthesis.